Stakeholder Perspectives on Returning Nonactionable Apolipoprotein L1 (APOL1) Genetic Results to African American Research Participants. (February 2022) - West, Kathleen M.; Cavanaugh, Kerri L.; Blacksher, Erika; Fullerton, Stephanie M.; Umeukeje, Ebele M.; Young, Bessie; Burke, Wylie
: The ethics of returning nonactionable genetic research results to individuals are unclear. Apolipoprotein L1 ( APOL1 ) genetic variants are nonactionable, predominantly found in people of West African ancestry, and contribute to kidney disease disparities. To inform ethical research practice, we interviewed researchers, clinicians, and African American community members ( n   =  76) about the potential risks and benefits of returning APOL1 research results. Stakeholders strongly supported returning APOL1 results. Benefits include reciprocity for participants, community education and rebuilding trust in research, and expectation of future actionability. Risks include analytic validity, misunderstanding, psychological burdens, stigma and discrimination, and questionable resource tradeoffs. : Conclusions: APOL1 results should be offered to participants. Responsibly fulfilling this offer requires careful identification of best communication practices, broader education about the topic, and ongoing community engagement.